Labor Market Policies and Outcomes: Cross Country Evidence for the EU-27 - Riccardo Rovelli; Randolph Bruno (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
We conduct a comparative analysis of Labor Market Policies and outcomes for the EU member states, for period 2000-2005. We document the main differences in Labor Market Policies across EU members, including new members states after 2004. We focus on indicators of policy generosity (expenditures relative do GDP) and relate these and other policy indicators to indicators of labor market outcomes and performance. Our results show that, on a cross-country basis, higher rates of employment are in general associated with: (i) higher expenditures on labor market policies, especially on active policies; (ii) a lower degree of rigidity in labor market institutions and in product market regulation.
Keywords: 330